ChemInform Abstract: Synthesis and Derivatization of Highly‐Functionalized λ5‐Phospholes. Issue 38 (10th September 2014) - Ruiz, Javier; Gonzalo, Marta P.; Vivanco, Marilin; Garcia‐Granda, Santiago
Abstract A variety of highly functionalized λ5‐phosphole derivatives are synthesized by regiospecific [3 + 2] cycloaddition reactions of diphosphinoketenimine (I) with electron‐poor alkenes.